The factors that influence student’s intention towards celebrity endorsement / Fairuz Nasri - Nasri, Fairuz (Faculty of Business and Management, 2018)
The purpose of study is to investigate the factors that influence student’s intention towards celebrity endorsement in UiTM Kampus Bandaraya Melaka. A review of the study in each area identifies key findings, collecting results and problem statement. In addition, this paper reviews the celebrity endorsement literature review with a focus on the factors that influence student’s intention. There are attitudes, subjective norms and perceived behavioural control as the independent variable while student’s intention towards celebrity endorsement as dependent variable.